(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
Unchecked levels of Reactive Oxygen Species (ROS) are known contributors in numerous health issues like metabolic disorders, neurological disorders and cancers. A traditional herbal preparation, Benincasa hispida Confection (BHC) is hypothesized to balance the levels ROS because of the presence of inherent antioxidative phytocomponents. However, the specific mechanisms underlying BHC purported ROS scavenging effects at cellular level have remained unexplored. We prepared BHC, and profiled its antioxidative molecules through HPLC analysis. Preparation method included B. hispida pulp base mixed with sugar candy and various medicinal herbs as key ingredients to enhance its taste and palatability. The ability to scavenge intracellular ROS was investigated using 2’,7’-dichlorofluorescin-diacetate (DCF-DA) assay after ensuring the cell viability upon treatment with the extract of BHC. BHC was rich in previously known antioxidant molecules and was able to quench intracellular ROS. B. hispida also contributed to its ROS quenching abilities along with other ingredients. This study provides valuable insights into the therapeutic utility of BHC and advocates that consumption of BHC might protect the individuals from the ROS mediated oxidative stress and associated diseases.